Five-year follow-up of drug utilization for secondary prevention in coronary artery disease - SANCAR, MESUT; RABUŞ, ŞULE (SPRINGER, 2008)
Objective Despite the availability of various prevention guidelines on coronary artery disease, secondary prevention practice utilizing aspirin, beta-blockers, angiotensin converting enzyme inhibitors and statins still can be sub-optimal. In this study, we aimed to assess the guideline adherence of secondary prevention prescribing and the continuity of adherence for a 5-year period in a small cohort of patients angiographically diagnosed to have coronary artery disease. Method In this prospective study, 73 patients who were angiographically diagnosed to have CAD were followed up for 5 years. The baseline demographic and clinical data were collected just before angiography. The baseline drug data were collected at the day of discharge. The fifth year data were taken from the patients via face-to-face consultations or phone interviews. Results The 'initial prescribing rate' at discharge was found to be 82% for aspirin, 49% for statins, 44% for ACE inhibitors and 55% for beta-blockers. 'Continuity of prescribing' for 5 years was 45% for aspirin, 26% for statins, 17% for ACE inhibitors and 20% for beta-blockers. Conclusions Besides the sub-optimal prescribing of secondary prevention drugs, absence of continuity of prescribing seems to be a challenging issue in pharmaceutical care of coronary artery disease patients.
Keywords: Drug Utilisation; Follow up; Guideline; Secondary prevention; Coronary disease; Turkey; ACUTE MYOCARDIAL-INFARCTION; CLINICAL-PRACTICE; IMPLEMENTATION; GUIDELINES; MANAGEMENT; DISCHARGE; OUTCOMES; UPDATE; CARE